Asuhan Keperawatan Pada Ny. S Dengan Hipertensi Di Ruangan Pejuang RSUD Bangkinang Tahun 2025 - Natasya, Bella; Aprilla, Nia; Alini, Alini; Virgo, Gusman (Jurnal Spektrum Kesehatan Indonesia, 2025)
Hypertension is a non-communicable disease caused by various factors such as excessive salt intake, stress, smoking, unhealthy diet, lack of physical activity, and family history. Often referred to as a “silent killer,” it typically presents without symptoms until serious complications arise. If left untreated, hypertension can result in circulatory disorders, pain, sleep disturbances, kidney damage, stroke, or heart failure. This scientific paper aims to describe the nursing care provided to Mrs. S, a 58-year-old patient diagnosed with hypertension and admitted to the Pejuang Ward of Bangkinang Regional Hospital. Data were collected through interviews, observation, physical examination, and document analysis. Three main nursing diagnoses were identified: ineffective peripheral perfusion, acute pain, and disturbed sleep pattern, all caused by uncontrolled high blood pressure. Nursing interventions were implemented using the Indonesian Nursing Intervention Classification (SIKI), focusing on pain management, circulatory care, and sleep support. Evaluation showed clinical improvement and enhanced patient understanding of hypertension management. Effective nursing care plays a crucial role in reducing the risk of complications and improving the overall quality of life for patients living with hypertension.